All the President's Senators: Presidential Copartisans and the Allocation of Federal Grants. Issue 2 (4th November 2016) - Christenson, Dino P.; Kriner, Douglas L.; Reeves, Andrew
Abstract : Previous scholarship argues that House members' partisan relationship to the president is among the most important determinants of the share of federal dollars they bring home to their constituents. Do presidential politics also shape distributive outcomes in the Senate? Analyzing the allocation of more than 8.5 trillion of federal grants across the states from 1984 to 2008, we show that presidential copartisan senators are more successful than opposition party members in securing federal dollars for their home states. Moreover, presidents appear to target grants ex post to states that gain presidential copartisans in recent elections.